Wybrane aspekty adaptacji nowego pracownika do systemu pracy w świetle badań empirycznych - Żarczyńska-Dobiesz, Agnieszka (Selected aspects of a new employee adaptation to a work system in the light of empirical research, 2006)
The article presents the results of the author’s research. The main aim is to present what the process of the induction of new employees is like and what it consists in. The research was conducted in about 150 Polish companies, different in the number of employees, the source of financial capital and the branch of activities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 153-166